Develop an RS-485 Protocol for Arduino Boards Applied To Networked Real Time Control Systems - Dang Long Tran; Truong Hoa Binh Nguyen; Nam Hoa Ho; Duy Anh Nguyen; Van Danh Tran; Minh Nhat Nguyen; Duc Chanh Tin Doan (Journal of Technical Education Science, 2024)
The Arduino microprocessor boards such as Mega 2560, UNO R3, Leonardo, Micro, and Nano are simple and low-cost tools for real-time measurement and control applications. These Arduino boards cannot be used in distributed systems because they lack the networking capabilities to transfer data across units. In this study, an RS-485 protocol for Arduino boards that operate in Master-Slave networks was developed. Network operations could be carried out independently on the main thread program, and devices in the network could react quickly to information received. This was made possible by the asynchronous serial communication feature and a high-speed timer provided in Arduino boards. The networks designed in this study were applied to an electric vehicle model with all-wheel drive and all-wheel steering capabilities for supermaneuverability as well as a saltwater intrusion early warning system installed in a river entry. The results showed that highly reliable and stable network operations could be achieved, thus extending the usage of popular Arduino boards for networked real-time applications.